Legal Aspects of Child Protection in the Perspective of National Law - Rianza Naufalfalah Ilham (CV. Rayyan Dwi Bharata, 2023)
Law Number 39 of 1999 concerning Human Rights in Chapter III Human Rights and Basic Human Freedoms in Part Ten regulates children's rights. The section entitled Rights of the Child provides regulatory provisions which are poured into 15 (fifteen) articles, where in Article 52 Paragraph (2) it is stated that children's rights are human rights and for the benefit of the child's rights are recognized and protected by law even since in the womb. The Unitary State of the Republic of Indonesia in ensuring the welfare of every citizen, one of which is to provide protection for children's rights which is one of human rights. The Indonesian government in its efforts to guarantee and realize the protection and welfare of children is through the establishment of Law Number 23 of 2002 concerning Child Protection. Child Protection as referred to in Article 1 point 2 of the Law is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and status, and receive protection from violence and discrimination. Legal protection and the concept of protection for children consist of several aspects including; protection of children's human rights and freedoms, protection of children in the judicial process, protection of children's welfare (in the family, educational and social environment), protection of children in cases of detention and deprivation of liberty, protection of children from all forms of exploitation (enslavement, child trafficking) , prostitution, pornography, trafficking/abuse of drugs, manipulating children in committing crimes and so on), protection of street children, protection of children from the effects of war/armed conflict, protection of children against acts of violence, special attention should be paid to children Problems with the Law (ABH) and the need for application and/or implementation of basic concepts for the protection of children's human rights.